Excitation energy transfer in divinylbenzene copolymers - Zhmurin, P.N.; Elyseev, D.A.; Titskaya, V.D.; Lebedev, V.N.; Adadurov, A.F. (Functional Materials, 2012)
This article describes our attempts to produce "nonexcimer" polymer systems by means of rigid fixation of chromophore groups positioned between two vinyl bonds. Divinylbenzene and methylmethacrylate copolymers were chosen as such systems. Study of the optical properties of synthesized copolymers showed their constancy in a wide region of specific concentrations of chromophore groups. The absence of luminescent properties modification in a wide concentrations range proves the possibility of eliminating the intrasystem energy traps by means of rigid fixation of chromophores in polymer.